ANALISIS KESUKSESAN IMPLEMENTASI â€œSAKTIâ€ DI LINGKUNGAN KORWIL PENGADILAN TINGGI BANGKA BELTUNG MENGGUNAKAN DELONE AND MCLEAN MODEL - Septiani, Dina; Anggita, Wenni; Ridwan, Muhammad Qomaruddin (Jurnal Akuntansi dan Pajak, 2024)
This research aims to measure the success of SAKTI implementation in twelve work units within the Regional Coordination Committee of the Bangka Belitung High Court using the DeLone and McLean information system success model. By using a saturated sampling technique, this research used the population, namely all SAKTI users in the Regional Coordination Committee of the Bangka Belitung High Court, as the sample. The method used is quantitative through a survey approach. The research results show that system quality and service quality have a positive effect on user satisfaction. Likewise, user satisfaction has a positive effect on net benefits. Meanwhile, information quality does not have a significant effect on user satisfaction